Nitric oxide modulates the cardiovascular effects elicited by acetylcholine in the NTS of awake rats - da Silva, Liana Gouveia; Dias, Ana Carolina Rodrigues; Furlan, Elaina; Colombari, Eduardo [UNESP] (Amer Physiological Soc, 2008)
da Silva LG, Rodrigues Dias AC, Furlan E, Colombari E. Nitric oxide modulates the cardiovascular effects elicited by acetylcholine in the NTS of awake rats. Am J Physiol Regul Integr Comp Physiol 295: R1774-R1781, 2008. First published September 24, 2008; doi:10.1152/ajpregu.00559.2007.-Microinjection of acetylcholine chloride (ACh) in the nucleus of the solitary tract (NTS) of awake rats caused a transient and dose-dependent hypotension and bradycardia. Because it is known that cardiovascular reflexes are affected by nitric oxide (NO) produced in the NTS, we investigated whether these ACh-induced responses depend on NO in the NTS. Responses to ACh (500 pmol in 100 nl) were strongly reduced by ipsilateral microinjection of the NOS inhibitor N(G)-nitro-L-arginine methyl ester (L-NAME; 10 nmol in 100 nl) in the NTS: mean arterial pressure (MAP) fell by 50 +/- 5 mmHg before L-NAME to 9 +/- 4 mmHg, 10 min after L-NAME, and HR fell by 100 +/- 26 bpm before L-NAME to 20 +/- 10 bpm, 10 min after L-NAME (both P < 0.05). Microinjection of the selective inhibitor of neuronal nitric oxide synthase (nNOS), 1-(2-trifluoromethylphenyl) imidazole (TRIM; 13.3 nmol in 100 nl), in the NTS also reduced responses to ACh: MAP fell from 42 +/- 3 mmHg before TRIM to 27 +/- 6 mmHg, 10 min after TRIM (P < 0.05). TRIM also tended to reduce ACh-induced bradycardia, but this effect was not statistically significant. ACh-induced hypotension and bradycardia returned to control levels 30-45 min after NOS inhibition. Control injections with D-NAME and saline did not affect resting values or the response to ACh. In conclusion, injection of ACh into the NTS of conscious rats induces hypotension and bradycardia, and these effects may be mediated at least partly by NO produced in NTS neurons.
Keywords: cholinergic transmission; nitric oxide synthase inhibition; nucleus of the solitary tract; cardiovascular control